International Conference on Color Confinement and Hadrons in Quantum Chromodynamics :The Institute of Physical and Chemical Research (RIKEN), Japan, 21-24 July 2003 /H. Suganuma ... [et al.]. - Hatsuda, T.
"The International Conference ... was held from July 21 to 24 in 2003 at the Institute of Physical and Chemical Research (RIKEN) with the host of Interactive Research Center of Science (IRCS) at Tokyo Institute of Technology"--Pref., p. vii.